PEMETAAN SISTEM PENGELOLAAN PENDIDIKAN MANAJEMEN BERBASIS SEKOLAH (SCHOOL BASED MANAGEMENT) - -, Sumarto (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2016)
This article makes a map of education management in school by looking at the developed potentials in every school elements, starting from the headmaster, teachers, education staffs and students. The potential contributed is the expectation of school. It is not only as a known list, but also to be implemented through good and correct map. Through school based management certainly it gives authority to head master to develop the school along the vision-mission and work-program which have been planned. Through descriptive analysis approach, this article conclude that school based management is a management paradigm which put forward an autonomy and involvement of community. Education autonomy means an effort to give a large space for the head master to develop and manage the institution. Furthermore, the education institution is expected to be able to find the relevance with the needs of the community by involving the community in taking and monitoring the education decree.Keywords; School based management, Education management system, Education quality, Public participation